The Importance of Mittelstand Firms for Regional Apprenticeship Activity - Vera Jahn (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2017)
German politicians frequently emphasize the importance of Mittelstand firms for the economy, thereby particularly referring to their enormous engagement in training apprentices. However, there is yet almost no empirical evidence on the question whether Mittelstand firms are in fact excessively active in training apprentices. We study whether the relative importance of owner-managed small and medium sized enterprises has an effect on firms' apprenticeship activity on the county level.
Keywords: C21; D23; I21; 330